2016
DOI: 10.3171/2015.9.spine15187
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent laryngeal nerve injury following reoperative anterior cervical discectomy and fusion: a meta-analysis

Abstract: OBJECTIVE Recurrent laryngeal nerve (RLN) injury is one of the most frequent complications of anterior cervical discectomy and fusion (ACDF) procedures. The frequency of RLN is reported as 1%–11% in the literature.4,15 The rate of palsy after reoperative ACDF surgery is not well defined. This meta-analysis was performed to review the current medical evidence on RLN injury after ACDF surgery and to determine a relative rate of RLN injury after reo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…As mentioned previously, the current literature documents an estimate of RLN injury of 14.1%. 16 Therefore, the major finding of this study is that when a 2-team surgical approach is applied to patients undergoing reoperative ACDF (those typically described as being at increased risk for VCP complications), these patients do not develop VCP complications at an increased rate. This finding supports the notion that a 2-team approach using an experienced head and neck surgeon can provide safe transcervical access for reoperative ACDF in patients at high risk for VCP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned previously, the current literature documents an estimate of RLN injury of 14.1%. 16 Therefore, the major finding of this study is that when a 2-team surgical approach is applied to patients undergoing reoperative ACDF (those typically described as being at increased risk for VCP complications), these patients do not develop VCP complications at an increased rate. This finding supports the notion that a 2-team approach using an experienced head and neck surgeon can provide safe transcervical access for reoperative ACDF in patients at high risk for VCP.…”
Section: Discussionmentioning
confidence: 99%
“…In that study the authors included a total of 238 patients in their analysis and concluded that the estimate of 14.1% for RLN palsy in reoperative ACDF surgery was greater than any estimated rate for primary procedures. 16 Although this provides a useful estimate, the limitations of the meta-analysis for estimating the rate of VCP are obvious. Without direct visualization of the vocal cords, accurate assessments of RLN injury and dysphonia are not attainable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Advantages of PCF are that the route of approach avoids the possible serious complications that can be accompanied with ACDF, such as injury to the carotid artery, the esophagus or recurrent laryngeal nerve [3][4][5]. PCF also allows to preserve mobility of the treated vertebral segments and does not include the use of implants.…”
Section: Introductionmentioning
confidence: 99%
“…However, oropharyngeal complications after ACDF such as dysphagia, hoarseness, or esophageal perforation may be still underestimated although they have been discussed in the literature. [ 8 9 10 11 12 13 14 15 16 17 18 19 20 21 ] Their frequency, severity, and possible eventual recovery after surgery need to be carefully considered. The purpose of this study is to investigate the incidence, severity, and possible risk factors for postoperative dysphagia recognized within 30 days after 1- or 2-level ACDF using a rectangular titanium stand-alone cage.…”
Section: Introductionmentioning
confidence: 99%